Relationship between Learning Motivation and Biology Learning Outcomes - Nurul Aulia Rahmi; Ramadhan Sumarmin; Yuni Ahda; Heffi Alberida; Abdul Razak (Jurnal Penelitian Pendidikan IPA, 2021)
This research is a descriptive correlation study that aims to reveal the relationship between learning motivation and learning outcomes of students' biology. This study uses a correlational study approach because it connects two variables, namely two independent variables in the form of learning motivation and the dependent variable in the form of biology learning outcomes of students. The technique used in sampling is purposive proportional random sampling, by determining the proportion according to the number of students in the school being studied. In this study, Pearson Product Moment using for conversion score analysis, score distribution, normality tests, and correlation analysis. This correlation analysis aims to determine the relationship between learning motivation and learning outcomes of biology. Furthermore, to see whether or not there is meaning in the research, the t-test is used and to see the contribution between the two variables using the coefficient determinant formula. The results show that there is a positive and meaningful relationship between learning motivation and learning outcomes of students in class X MIPA SMAN in Padang City with the value of tcount are 7.603, at the level of confidence 95% with db = 285, greater than ttable which is 1.650